Participação social e políticas públicas de extensão rural em assentamentos de reforma agrária - Zarnott, Alisson Vicente (2016)
Social participation is seen as the success cornerstone of the public policies, counting on the beneficiary public in its formulation, operationalization and co-management. The public policy of Rural Extension for Settlements is summed up in 2003 with the Technical, Social and Environmental Advisory Program that, in the settlements of Rio Grande do Sul, currently attends - through contracts signed with entities that provide rural extension services, defined through public calls - approximately eleven thousand families, organized in twenty Operational Nuclei. The current institutional format of the TSEA RS Program includes a State Board of TSEA, TSEA Regional Councils and evaluation and planning meetings in all the settlements. The present study investigated whether the changes that the program underwent during the contracts period (2009-2016) were derived from the process of social participation, and what other results were produced by the participation in the construction of a learning capable of subsidizing public discussions about the Program of TSEA and the other public policies of Rural Extension. The Habermasian theoretical reference on the public sphere, the theory of communicative action and deliberative democracy were used as analytical lens. Considering the criticisms of some elements of this theoretical body, the analysis with the contributions of Nancy Fraser on strong publics, weak publics and subaltern publics was complemented, allowing recognizing the multiplicity of publics, the difference of power and, nevertheless, the sphere Take the form of discussions and deliberations, contributing to the democratic construction. The research was anchored in action research and used action observation, documentary analysis and interviews. The main conclusions are that participation, role differentiation, networking and the construction of methodological tools for participation and qualification are key elements for a Pluralist Rural Extension System and a democratic Rural Extension program. Specifically on TSEA RS, participation was fundamental to achieve deliberative processes and the current design of the Program, allowing to provide references on the five dimensions analyzed: institutional design, context and institutional environment, inclusion and representativeness, deliberative process and results of participation.